2018
DOI: 10.1111/jhn.12561
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate knowledge, lifestyle and insulin: an observational study of their association with glycaemic control in adults with type 1 diabetes

Abstract: The present study identified that consistency in taking insulin and confidence in self-management was associated with better glycaemic control. An association was also found between recent dietary review and better carbohydrate knowledge, although this did not translate into better glycaemic control. Future investigation into the application of carbohydrate knowledge is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
(26 reference statements)
1
10
0
Order By: Relevance
“…Several analyses reported that insulin dose omission or mistiming of doses were associated with higher levels of HbA1c. 27,29,33,37,38,40,45,46,49,52 PwD appear to be aware of the detrimental impact of suboptimal dosing; 65% of European GAPP2 participants recognized that missing basal insulin doses would negatively affect their health. 19 Furthermore, a substantial proportion of PwD indicated that they felt worried or guilty about missing doses.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several analyses reported that insulin dose omission or mistiming of doses were associated with higher levels of HbA1c. 27,29,33,37,38,40,45,46,49,52 PwD appear to be aware of the detrimental impact of suboptimal dosing; 65% of European GAPP2 participants recognized that missing basal insulin doses would negatively affect their health. 19 Furthermore, a substantial proportion of PwD indicated that they felt worried or guilty about missing doses.…”
Section: Discussionmentioning
confidence: 99%
“…Missed insulin doses were consistently reported to be associated with higher HbA1c levels in people with T1D. 27,29,33,37,38,45,46 Similarly, in the GAPP2 study in people with T2D, HCPs indicated that missed insulin doses were associated with negative clinical effects, reporting that ~3-4 missed basal insulin doses per month significantly impacted glycemic control. [19][20][21] data are more limited, it was suggested by two studies that missed insulin doses may be negatively associated with health-related quality of life in adolescents with T1D 37 and adults with T2D.…”
Section: Association Between Missed Doses and Clinical Outcomesmentioning
confidence: 99%
See 3 more Smart Citations